Innovations Driving the Future of Maxillofacial Prosthetics, Part I: The Technological Leap in Maxillofacial Rehabilitation - Fayad, Mostafa I.; Ahmed, Mohamed Ashour; Kothayer, Marwa; Aboelnagga, Mona M.; Essa, Emad El Said Fahim; Abu-Hammad, Osama; Moussa, Rania (European Journal of Dentistry, 2025)
Maxillofacial prosthetics is a specialized field focused on replacing part or all of the facial and cranial structures. In recent years, digital technology has gained popularity over traditional methods for fabricating maxillofacial prostheses. This study aimed to provide a comprehensive review of recent innovations in maxillofacial prosthetic rehabilitation, with an emphasis on emerging technologies and their impact on patient outcomes, treatment efficiency, and overall quality of life.A comprehensive literature search was conducted across the Web of Science, PubMed, MEDLINE, and CENTRAL databases for studies published in English within the last decade. The keywords utilized included “Maxillofacial Prosthesis Implantation,” “Maxillofacial Prosthesis,” and “rehabilitation,” as well as “Virtual Rehabilitation,” “Artificial intelligence,” and “digital technology.” The initial search yielded 178 articles. After resolving 51 duplicates, 127 articles were screened based on titles and abstracts. Following full-text assessment, 81 articles met the inclusion criteria and were included in the review.The results indicated that advancements in digital technologies, digital imaging, data acquisition, and the integration of digital workflows have significantly transformed the rehabilitation of maxillofacial prosthetics. These innovations enabled customization and personalization, provided an improved fit, enhanced precision, reduced number of visits and chair time, and facilitated seamless rehabilitation of complex maxillofacial defects. Four-dimensional printing involves materials that can change shape or properties over time, enabled printed objects to adapt dynamically to external stimuli, enhancing both comfort and functionality of prosthetics. Further advancements, such as five-dimensional and six-dimensional printing, improved the sensory capabilities of prostheses. Virtual and augmented reality enhance real-world experiences by overlaying digital data, improving accuracy and fit, enabling virtual surgical planning, and developing patient-specific implants. Artificial intelligence (AI) assists automated decision-making and supports the design of AI-driven prostheses. AI algorithms have shown the potential to automate digital planning, replicate intricate anatomical features, and attain high diagnostic accuracy in maxillofacial prosthodontic scenarios.
Keywords: maxillofacial prosthesis; digital technology; artificial intelligence; augmented reality; 3D printing; virtual reality